Evaluating the impact of dividend restrictions on euro area bank market values - Desislava Andreeva; Paul Bochmann; Julius Schneider (European Central Bank (ECB), 2023)
This paper evaluates the impact of the March 2020 European Central Bank recommendation that banks do not pay dividends or buy back shares on their market values. It documents a causal negative impact on bank share prices of around 7% during the two weeks following its announcement. The recommendation affected the market values of banks directly, by delaying investor cash flows and indirectly, by increasing the uncertainty about future distributions and thus banks' equity risk premia. The impact differed across banks depending on their distribution plans and risk-adjusted profitability. Our analysis highlights the importance of managing perceptions about dividend uncertainty through credible communication about the expected duration, frequency and severity of dividend restrictions to limit their unintended side effects.
Keywords: G12; G21; G28; G35; 330; bank dividends; banking supervision; bank capital; COVID-19 pandemic; bank cost of equity